Disentangling the Effect of Pressure and Mixing on a Mechanochemical Bromination Reaction by Solid‐State NMR Spectroscopy. Issue 12 (20th January 2023) - Bartalucci, Ettore; Schumacher, Christian; Hendrickx, Leeroy; Puccetti, Francesco; d'Anciães Almeida Silva, Igor; Dervişoğlu, Rıza; Puttreddy, Rakesh; Bolm, Carsten; Wiegand, Thomas
Abstract: Mechanical forces, including compressive stresses, have a significant impact on chemical reactions. Besides the preparative opportunities, mechanochemical conditions benefit from the absence of any organic solvent, the possibility of a significant synthetic acceleration and unique reaction pathways. Together with an accurate characterization of ball‐milling products, the development of a deeper mechanistic understanding of the occurring transformations at a molecular level is critical for fully grasping the potential of organic mechanosynthesis. We herein studied a bromination of a cyclic sulfoximine in a mixer mill and used solid‐state nuclear magnetic resonance (NMR) spectroscopy for structural characterization of the reaction products. Magic‐angle spinning (MAS) was applied for elucidating the product mixtures taken from the milling jar without introducing any further post‐processing on the sample. Ex situ 13 C‐detected NMR spectra of ball‐milling products showed the formation of a crystalline solid phase with the regioselective bromination of the S ‐aryl group of the heterocycle in position 4. Completion is reached in less than 30 minutes as deduced from the NMR spectra. The bromination can also be achieved by magnetic stirring, but then, a longer reaction time is required. Mixing the solid educts in the NMR rotor allows to get in situ insights into the reaction and enables the detection of a reaction intermediate. The pressure alone induced in the rotor by MAS is not sufficient to lead to full conversion and the reaction occurs on slower time scales than in the ball mill, which is crucial for analysing mixtures taken from the milling jar by solid‐state NMR. Our data suggest that on top of centrifugal forces, an efficient mixing of the starting materials is required for reaching a complete reaction. Abstract : The mechanochemical bromination of a heterocyclic sulfoximine is studied by ex‐ and in situ solid‐state NMR spectroscopy. A selective and fast reaction is observed in a mixer mill, which can alternatively be induced either using the centrifugal pressure of magic‐angle spinning or by solely magnetic stirring the solid entities.